COMPUTATIONAL DETERMINATION OF REACTION MECHANISM OF CYCLOHEXENE DEHYDROGENATION ON COAL - Al-Rasyid (NIM : 105 00 0160, Hasan
Abstract: In the development of hydrogen application in fuel cells, there are many inventions in the field of hydrogen production and storage. Based on previous research, hydrogen can be produced through dehydrogenation of cyclohexene with anthracite coal as catalyst. This research focused on mechanism of that reaction. The mechanism was studied computationally, involving two models of coal active sites, i.e. armchair and zigzag. The entire computations were based on unrestricted Hartre Fock (UHF) method with basis set of 6-31G(d). From the calculations, the monoradical path were proposed as the most energetically favorable path for armchair model, and the biradical path were proposed for zigzag model. The two reaction paths were suspected to have approximately equal probability to occur because of their small difference in activation energy. Some influences to mechanisms that arise from different active site models were discussed.